DOP06 Antibiotics as a risk factor for older onset IBD: A population-based cohort study. (21st January 2022) - Faye, A; Allin, K; Iversen, A; Agrawal, M; Faith, J; Colombel, J F; Jess, T
Abstract: Background: Older adults are the fastest growing subpopulation of patients with IBD, with approximately 15% diagnosed after 60 years-of-age. Moreover, environmental exposures are thought to play a significant role in the development of older-onset IBD, given the lower genetic risk. Antibiotics have been associated with development of IBD in earlier generations, but the impact on IBD risk in older adults is uncertain. In this population-based cohort study, we assessed the impact of cumulative antibiotic use, the timing of antibiotic use, and the association between specific antibiotic classes and the development of older-onset IBD. Methods: Using Denmark nationwide registries, a cohort of residents ≥60 years-of-age was established between 2000–2018. Information on exposure to antibiotics was retrieved from the Danish National Prescription Register. The number of courses of antibiotics (overall and specific classes) was considered a time-varying variable. The outcome, IBD, was identified based on ICD-10 codes in the Danish National Patient Register. Incidence rate ratios (IRRs) for IBD according to antibiotic use 1 to 5 years prior to IBD diagnosis were calculated by log-linear Poisson regression, and adjusted for age, sex, and calendar period. Results: There were a total of 2, 327, 796 individuals aged 60 to 90 years included in the cohort, resulting in 22, 670, 484 person-years of follow-up. There were 10, 773 new cases of ulcerative colitis (UC) and 3, 825 new cases of Crohn's disease (CD). Overall, any antibiotic use was associated with an IRR for the development of IBD (IRR 1.64, 95%CI 1.58–1.71), with a positive dose response observed (1 course of antibiotics IRR 1.27 95%CI 1.21–1.33; 2 courses IRR 1.54 95%CI 1.46–1.63; 3 courses IRR 1.66 95%CI 1.67–1.77; 4 courses IRR 1.96 95%CI 1.83–2.09; 5+ courses IRR 2.35, 95%CI 2.24–2.47). A higher IRR was noted between the timeframe of 1–2 years before diagnosis (IRR 1.87, 95%CI 1.79–1.94) as compared to 2–5 years before diagnosis (IRR 1.42, 95%CI 1.36–1.48). Additionally, all antibiotic classes were associated with the development of IBD, including those not used to treat gastrointestinal infections. Antibiotics with the highest IRR were fluoroquinolones (IRR 2.27, 95%CI 2.08–2.48), nitroimidazoles (IRR 2.21, 95%CI 1.95–2.50), and macrolides (IRR 1.74, 95%CI 1.64–1.84). All results remained statistically significant when stratifying by UC and CD, with effect estimates slightly higher for CD as compared to UC. Conclusion: Use of antibiotics, regardless of class studied, was associated with an increased risk of older-onset IBD. This risk was highest one to two years prior to diagnosis, but persisted even prior to that, suggesting a link between overall antibiotic use and development of older-onset IBD.